Unit operations of chemical engineering - McCabe, Warren L. (Mc Graw Hill, 2001)
The book is written in a practical manner for the education of B.S.-level chemical engineers. It introduces students to common equipment and gives them the basic concepts of operation both qualitatively and quantitatively. A solid theoretical foundation enables students to understand basic phenomena underlying the unit operations but real-world applications are also sufficiently covered.